2019
DOI: 10.21834/e-bpj.v4i11.1742
|View full text |Cite
|
Sign up to set email alerts
|

Practice and Knowledge of Contact Lens Use Among Medical Students of Universiti Teknologi MARA

Abstract: Contact lens is an optical device that is commonly used to correct refractive errors of the eye. Improper care may lead to ocular related complications. This was a descriptive study to assess contact lens care practice and knowledge on contact lens use among medical students of Universiti Teknologi MARA (UiTM). Out of seven proper practices of contact lens care listed, only hand washing practice was adhered by most of the wearer. Both groups of contact lens wearer and non-wearers showed a moderate level of kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…21 In the present study, the prevalence of CL usage among university students was found to be 46%, similar to the previous studies published between 2014 and 2018, ranging from 40.2% to 44.8%. 2,7 Studies have also reported that the prevalence of CL wearers among medical students ranged from 14.0% to 38.0% and was similar to the present study, 39% in medical students 2,12,14,22,23 Interestingly, the prevalence of CL wearers in the non-medical student group was higher (46.8%). About half of CL users in this survey were new users with a history CL handling.…”
Section: Discussionsupporting
confidence: 87%
“…21 In the present study, the prevalence of CL usage among university students was found to be 46%, similar to the previous studies published between 2014 and 2018, ranging from 40.2% to 44.8%. 2,7 Studies have also reported that the prevalence of CL wearers among medical students ranged from 14.0% to 38.0% and was similar to the present study, 39% in medical students 2,12,14,22,23 Interestingly, the prevalence of CL wearers in the non-medical student group was higher (46.8%). About half of CL users in this survey were new users with a history CL handling.…”
Section: Discussionsupporting
confidence: 87%